Human Rights Manifestation Through Enforcement of Communal Land Ownership Rights for Women in Minangkabau - Tafkir Tafkir (HUMANISMA : Journal of Gender Studies, 2021)
A complex issue that is very difficult to unravel in the Minangkabau community is about communal land as a high inheritance according to Minangkabau customs. In Minangkabau custom, the land is women's right, but in control and who takes the lead to maintain land tend to cause dispute between men and women in its development and utilization. High inheritance assets that women should own should be fully controlled and utilized by the brothers. Meanwhile, women must be willing to leave the clan to find residential or agricultural land. This problem becomes more acute when economic problems and social stratification are carried away in the dialogue. Often the rights that women should naturally receive in Minangkabau are crippled by gender stratification developed by brothers who feel more powerful and feel physically and economically stronger. Persoalan pelik yang sangat susah diurai dalam masyarakat Minangkabau adalah persoalan tanah ulayat sebagai harta pusaka tinggi menurut adat Minangkabau. Dalam adat Minangkabau, tanah adalah hak perempuan, namun dalam pengawasaan dan penguasaan sering kali timbul silang sengketa antara laki-laki dan perempuan dalam penguasaan dan pemanfaatannya. Harta pusaka tinggi yang seyogyanya dimililiki oleh perempuan dikuasai dan dimanfaatkan secara penuh oleh saudara laki-laki. Sementara perempuan harus rela keluar dari kaum untuk mencari lahan pemukiman atau pertanian. Persoalan ini semakin meruncing ketika persoalan ekonomi dan kekuatan stratifikasi sosial terbawa dalam dialog tersebut. Sering kali hak yang seharusnya diterima perempuan secara asasi di Minangkabau terkebiri oleh strafikasi gender yang dikembangkan oleh saudara laki-laki yang merasa lebih berkuasa dan merasa lebih kuat secara fisik dan ekonomi.